Beyond Exhibits : Exploring Museum VR Adoption through a Validated UTAUT2 Model for Visitor Usage Behaviour - Li, Yi Fei; Mohd Kamal, Othman (UNIMAS Publisher, 2024)
This study examines the Unified Theory of Acceptance and Use of Technology (UTAUT2) model's suitability for understanding museum visitors' intentions towards Virtual Reality (VR) technology. Compared to the Technology Acceptance Model (TAM), UTAUT2 offers a more comprehensive framework. The study validates its relevance to the museum context and extends it with factors such as design quality and past experience. A questionnaire based on this extended model was developed and validated with 78 participants. The results confirm the model's effectiveness and reliability, suggesting its potential for studying VR intentions in museums. This validated model lays the groundwork for future large-scale studies exploring generational differences in VR usage through age-segmented data analysis. Understanding these variations can inform the development of VR experiences tailored to specific age groups, ultimately enhancing the museum experience.